2022
DOI: 10.1039/d2ee00887d
|View full text |Cite
|
Sign up to set email alerts
|

Identifying structure–absorption relationships and predicting absorption strength of non-fullerene acceptors for organic photovoltaics

Abstract: Non-fullerene acceptors (NFAs) are excellent light harvesters, yet the origin of such high optical extinction is not well understood. In this work, we investigate the absorption strength of NFAs by...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 94 publications
2
30
0
Order By: Relevance
“…From BTP-PhC6 to BTP-PhC6-C11 to Y6 , the absorption strength gradually increases, which may be related to the gradual improvement of the molecular planarity. 59 From solutions to films, Y6 and BTP-PhC6-C11 exhibit similar and more remarkable redshifts (85 nm for Y6 and 84 nm for BTP-PhC6-C11 ) relative to that of BTP-PhC6 (77 nm), which are ascribed to the distinct aggregation behavior of these three SMAs in the solid state. The extinction coefficients of Y6 , BTP-PhC6-C11 , and BTP-PhC6 in the solid state were about 1.07 × 10 5 , 1.05 × 10 5 and 0.98 × 10 5 cm −1 , respectively, which exhibits the same trend as that in CF solution.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…From BTP-PhC6 to BTP-PhC6-C11 to Y6 , the absorption strength gradually increases, which may be related to the gradual improvement of the molecular planarity. 59 From solutions to films, Y6 and BTP-PhC6-C11 exhibit similar and more remarkable redshifts (85 nm for Y6 and 84 nm for BTP-PhC6-C11 ) relative to that of BTP-PhC6 (77 nm), which are ascribed to the distinct aggregation behavior of these three SMAs in the solid state. The extinction coefficients of Y6 , BTP-PhC6-C11 , and BTP-PhC6 in the solid state were about 1.07 × 10 5 , 1.05 × 10 5 and 0.98 × 10 5 cm −1 , respectively, which exhibits the same trend as that in CF solution.…”
Section: Resultsmentioning
confidence: 93%
“…From BTP-PhC6 to BTP-PhC6-C11 to Y6, the absorption strength gradually increases, which may be related to the gradual improvement of the molecular planarity. 59 From solutions to films, Y6 and BTP-PhC6-C11 exhibit similar and more remarkable redshifts (85 nm for Y6 and 84 nm for BTP-PhC6-C11) relative to that of BTP-PhC6 (77 nm), which are ascribed to the distinct aggregation behavior of these three SMAs in the solid state.…”
Section: Optical and Electrochemical Propertiesmentioning
confidence: 93%
“…High absorption should, in principle, lead to strong emission due to the reciprocity relationship between absorption and emission, lowering nonradiative energy losses and benefiting open-circuit voltage. For identifying structure–absorption relationship, Nelson et al 141 investigated 500 unique organic molecules with DFT and TDDFT to study absorption strength and unravel structural features that lead to high absorption strength. The authors found that the absorption strength calculated experimentally and by TDDFT is in good agreement for NFAs and fullerene and suggested the use of TDDFT calculations for further modeling.…”
Section: Review Of ML In Osc Researchmentioning
confidence: 99%
“…16,17 ML models have been used in OSCs to investigate novel active materials and the information concealed in their chemical structures. 18 Traditionally, trialand-error approaches based on intuition have remained the primary way to design novel materials. It would take years to explore a large chemical space of materials.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, machine learning (ML) is gaining much attention, given its ability to accelerate productivity and material discovery. , ML models have been used in OSCs to investigate novel active materials and the information concealed in their chemical structures . Traditionally, trial-and-error approaches based on intuition have remained the primary way to design novel materials.…”
Section: Introductionmentioning
confidence: 99%